Cluster-Based TDMA Broadcast MAC Protocol for Mobile Ad-Hoc - Pandey Ananta (The Graduate School, Ajou University, 2010)
We have witnessed explosive growth in wireless networks over the last few years. Despite of their improved flexibility and reduced costs there are some challenges in Mobile Ad-hoc network like energy constrained, frequent topology changes and network partitions due to mobility and most importantly limited frequency and broadcast nature of wireless medium which introduces the hidden terminal and exposed terminal problems. Multi-hop Broadcasting is a general procedure to solve many issues in Mobile Ad-hoc network. In particular, due to node mobility the broadcasting is expected to be executed more frequently for finding a route to particular host, to maintain network, to have network information updates and for real time voice broadcast for particular applications. Especially mobile ad hoc network can be used in special set of applications where we do not have infrastructure support. Some situations like battle field or disaster areas where networks need to be established immediately and base stations or fixed network infrastructure are not available. This research is conducted for real time voice broadcasting in multi-hop wireless network. In this research we introduced a new approach to broadcast real time voice traffic with clustering and Time Division Multiple Access (TDMA). Time is divided in sequence of super-frame. Cluster head selects a frame from super-frame which supposed to be the unique frame than its neighbor clusters. So while one cluster is on transmission schedule basically there won？t be any other neighbor cluster on transmission. The overlapping clusters results some nodes to hear more than one cluster-head so are called relay nodes. Relay nodes always relay message from one cluster-head to other. Before going for transmissions relay nodes and source nodes need to reserve data slot. Transmitting nodes use a contention slot to reserve data slot. Since the network is divided in overlapping clusters and no neighbor cluster has same frame and all the transmitting nodes in a frame has their own data slot we are assured that there is no collision in data slot which will save considerable amount of power moreover every nodes does not need to transmit, only relay one relay node transmits a packet for a cluster and the cluster-head broadcast it to its range. Since minimal number of nodes takes part in transmitting of a packet, all the network resources could be saved as well.
학위논문(석사)--아주대학교 일반대학원 :컴퓨터공학과,2010. 2
Keywords: cluster-based TDMA; broadcast MAC protocol; mobile Ad-Hoc